PENGAWASAN INPEKSI MENDADAK DEWAN PERWAKILAN RAKYAT DAERAH PEKANBARU TERHADAP TEMPAT KARAOKE TAHUN 2017-20018 - Purwadi Wibowo; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
That the DPRD's supervisory function in Pekanbaru City towards the implementation of Regional Regulation No.03 of 2002 concerning the Regulation of the Recreation and Public Entertainment Business, is a challenge for members of the Pekanbaru City DPRD as a forum for the aspirations of the people who have a function in policy oversight carried out by the Pekanbaru city government to keep it running according to legal and social corridors. However, in the case of the implementation of supervision carried out by members of the Pekanbaru City DPRD in its implementation, it often finds the same problem, this is evident that there are still many findings from the inspection of violations committed by night entertainment venues that do not comply with the rules stipulated in Pekanbaru City Regulation No. 03 of 2002 , related to operating hours and functions of night entertainment venues. The number of violations committed by the management of entertainment venues in their sudden inspection conducted by the manager reasoned that the operating hours set in the Pekanbaru City Regulation No. 03 of 2002, made the visitors quiet and hoped for additional hours related to their business operations. For this reason, they also manage nightclubs, assuming Perda No. 03 of 2002 discourages outside investors from entering and leaving visitors deserted. Then, for this oversight function to be able to reduce the occurrence of irregularities, it means that the Pekanbaru City DPRD must be able to straighten out policies based on existing functions and rules and carry out the supervisory function of Perda No. 03 of 2002 especially in Pekanbaru CityKeywords: Oversight, Coordination, Sanctions and Policy Formulation